2002
DOI: 10.4324/9780203187821
|View full text |Cite
|
Sign up to set email alerts
|

Marketing, Morality and the Natural Environment

Abstract: ii FOREWORD iv

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 148 publications
(490 reference statements)
0
21
0
Order By: Relevance
“…Moral muteness was famously illustrated by social psychologists in the Stamford Prison Experiment, where the 'good' guards didn't report their more brutal colleagues to the researchers in charge of the experiment, their silence making them complicit in the unnecessarily bad treatment of the poor students who had been randomly selected as prisoners (Zimbardo et al, 2000) and has also been linked with group-think (Janis, 1982;Maclagan, 1998, p. 117). This desire to be seen to be ''fitting in'' with a prevailing amoral organizational culture has been evidenced by management researchers, who have identified the perceived ''futility'' of attempting to influence top management to operate in a socially responsible manner (Collins and Ganotis, 1973;Lincoln, et al, 1982;Lovell, 2002a), or, who have found that ethical arguments and moral discourse are ''reframed'' into the more commonly accepted commercial language of business organizations (Catasus, et al, 1997;Crane, 2000;Crane, 2001;Desmond and Crane, 2004;Gabriel et al, 2000, chapter 5;Lovell, 2002b). It should come as no surprise to us, then, that the headline-grabbing examples of corporate misdemeanor continue to emerge, if indeed corporations are largely populated by amoralized managers (Carroll, 1987) in a modern business world that ''...places business needs above individual morality...'' (Hendry, 2004, p. 181).…”
Section: The Myth Of Individual Moral Agency?mentioning
confidence: 94%
See 1 more Smart Citation
“…Moral muteness was famously illustrated by social psychologists in the Stamford Prison Experiment, where the 'good' guards didn't report their more brutal colleagues to the researchers in charge of the experiment, their silence making them complicit in the unnecessarily bad treatment of the poor students who had been randomly selected as prisoners (Zimbardo et al, 2000) and has also been linked with group-think (Janis, 1982;Maclagan, 1998, p. 117). This desire to be seen to be ''fitting in'' with a prevailing amoral organizational culture has been evidenced by management researchers, who have identified the perceived ''futility'' of attempting to influence top management to operate in a socially responsible manner (Collins and Ganotis, 1973;Lincoln, et al, 1982;Lovell, 2002a), or, who have found that ethical arguments and moral discourse are ''reframed'' into the more commonly accepted commercial language of business organizations (Catasus, et al, 1997;Crane, 2000;Crane, 2001;Desmond and Crane, 2004;Gabriel et al, 2000, chapter 5;Lovell, 2002b). It should come as no surprise to us, then, that the headline-grabbing examples of corporate misdemeanor continue to emerge, if indeed corporations are largely populated by amoralized managers (Carroll, 1987) in a modern business world that ''...places business needs above individual morality...'' (Hendry, 2004, p. 181).…”
Section: The Myth Of Individual Moral Agency?mentioning
confidence: 94%
“…Furthermore, this higher level of commitment to CSR requires that all employees elect to take some personal moral responsibility for their contribution to all their firm's activities: in terms of their impact on people both within and outside of the corporation; directly and indirectly over and above their contribution to their firm's economic success. This difficulty is reflected in the management literature and is, arguably, compounded by the view that some managers may be amoral (Crane, 2000;Harris and Crane, 2002;Lovell, 2002a).…”
Section: Corporate Social Irresponsibilitymentioning
confidence: 96%
“…The literature shows that firms have taken different approaches to green marketing activities (Baker and Sinkula, 2005a;Baker and Sinkula, 2005b;Crane, 2000b;Drumwright, 1994;Hudson and Miller, 2005;Kärnä et al, 2003;Menon and Menon, 1997;Polonsky and Rosenberger, 2001). In many cases, firms claim to embrace Business Environmental Responsibility (BER) because they realize that this is the right thing to do and perceive they have a duty to behave in a socially responsible manner-in other cases because they come under stakeholder pressure, and clearly many will fall in between.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Those misleading green marketing claims -green-washing-lead to consumer scepticism towards all claims, minimising the benefits to truly committed companies who seek to promote the environmental attributes of their products in the marketplace (Chamorro and Bañegil, 2006;Crane, 2000b;Polonsky and Rosenberger, 2001). …”
Section: Literature Reviewmentioning
confidence: 99%
“…An increasingly debated consumer issue -both in academia and among various stakeholders -is whether, or how, the market can function in new ways as a political arena, and to what extent consumers can use the market to become (sub) politically active (see Crane, 2000;Sørensen, 2002:7) 42 . The basic questions are not entirely new: Should we perceive consumerism as an ideal form of political participation and empowerment where 'every penny gives a right to vote ' (von Mises, 1944:17;cf., Cohen, 1990:xii) thus constituting 'the authority of the consumer' (Slater 1997:51)?…”
Section: Introductionmentioning
confidence: 99%